2016
DOI: 10.1134/s0006297916100151
|View full text |Cite
|
Sign up to set email alerts
|

Participation of two carbonic anhydrases of the alpha family in photosynthetic reactions in Arabidopsis thaliana

Abstract: The expression of genes of two carbonic anhydrases (CA) belonging to the α-family, α-CA2 and α-CA4 (according to the nomenclature in N. Fabre et al. (2007) Plant Cell Environ., 30, 617-629), was studied in arabidopsis (Arabidopsis thaliana, var. Columbia) leaves. The expression of the At2g28210 gene coding α-CA2 decreased under increase in plant illumination, while the expression of the At4g20990 gene coding α-CA4 increased. Under conditions close to optimal for photosynthesis, in plants with gene At2g28210 kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…The knockout of α-ca2 gene has led to the opposite changes in the properties of plants compared with those resulting from the knockout of α-ca4 gene. Fresh leaf weight, chlorophyll a/chlorophyll b ratio, and starch and H 2 O 2 content in leaves of α-CA2 mutants were lower than in the WT plants, while CO assimilation rate was higher [37,134,135]. In α-CA2 knockouts, the effective quantum yield of photosynthetic electron transport was lower than in WT, while NPQ was higher, also due to the energy-dependent component.…”
Section: Ca In Granal Thylakoid Membranesmentioning
confidence: 85%
See 2 more Smart Citations
“…The knockout of α-ca2 gene has led to the opposite changes in the properties of plants compared with those resulting from the knockout of α-ca4 gene. Fresh leaf weight, chlorophyll a/chlorophyll b ratio, and starch and H 2 O 2 content in leaves of α-CA2 mutants were lower than in the WT plants, while CO assimilation rate was higher [37,134,135]. In α-CA2 knockouts, the effective quantum yield of photosynthetic electron transport was lower than in WT, while NPQ was higher, also due to the energy-dependent component.…”
Section: Ca In Granal Thylakoid Membranesmentioning
confidence: 85%
“…α-CA1 was discovered in chloroplast stroma [10], and α-CA4 was found during proteomic studies among the proteins of the thylakoid membranes [35,36]. Evidence suggests that α-CA2 is present in thylakoid membranes [37]. α-CA3 was found in flowers and pods [5], as well as during proteomic analysis of mature pollen proteins [38,39].…”
Section: α-Casmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the quantum yield at photosystem 2 (PS2) and the electron transfer to O 2 decreased while non-photochemical quenching (NPQ) and CO 2 assimilation were enhanced in plants lacking αCA2. The opposite was observed in αCA4 knock-outs [ 155 ]. The authors hypothesize that these αCAs may participate in the regulation of H + flux into the PS2 protein PsbS, which regulates qE-type NPQ.…”
Section: Formation and Use Of Bicarbonate In Plantsmentioning
confidence: 99%
“…This protein plays a vital role in the early event of photosynthesis. Zhurikova et al (2016) indicated that the reduction of the activity of CA affected the effective quantum yield of photosystem II, thus, its low abundance might weaken photosynthesis in the phytoplasma-infected plants.…”
Section: Discussionmentioning
confidence: 99%